2018
DOI: 10.1016/j.theriogenology.2018.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Improved embryo development using high cysteamine concentration during IVM and sperm co-culture with COCs previous to ICSI in bovine

Abstract: In contrast to other species, intracytoplasmic sperm injection (ICSI) in bovine remains inefficient, resulting in low embryo developmental rates. It is unclear whether such inefficiency is due to the poor response of bovine ooplasms to the injection stimulus, or to the inability of bull sperm to induce oocyte activation. In order to facilitate these events, two strategies were assessed: the use of high concentration of cysteamine [Cys] during IVM; and the selection of sperm attached to cumulus cells after incu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 61 publications
1
10
0
Order By: Relevance
“…These data indicated that cysteamine supplementation was presumable could increase GSH concentration either for protection from ROS or to improve fertilization rate. This is confirmed by Canel et al (2018) that cysteamine supplementation during IVM, competent oocytes could increase their ability to synthesize GSH, facilitating the replacement of sperm protamins by histones during the male pronuclear formations. Although cysteamine in concentration 50 µm could not increase nuclear maturation, however it is presumable could increase oocyte quality, thus improve fertilization rate.…”
Section: Discussionmentioning
confidence: 62%
“…These data indicated that cysteamine supplementation was presumable could increase GSH concentration either for protection from ROS or to improve fertilization rate. This is confirmed by Canel et al (2018) that cysteamine supplementation during IVM, competent oocytes could increase their ability to synthesize GSH, facilitating the replacement of sperm protamins by histones during the male pronuclear formations. Although cysteamine in concentration 50 µm could not increase nuclear maturation, however it is presumable could increase oocyte quality, thus improve fertilization rate.…”
Section: Discussionmentioning
confidence: 62%
“…After IVM, about 10 matured COCs per drop were co‐incubated with sperm for 5 h at 38.5°C under 5% CO 2 in humidified air. This IVF protocol using a high sperm concentration and a short period of gametes co‐incubation was the same used by other authors (Canel et al, 2018; Hiriart et al, 2013; Vichera et al, 2011) and the one we used in previous studies (Barrera et al, 2018; García et al, 2015) obtaining results within standard parameters. Following the IVF period, presumptive zygotes were harvested from the insemination droplets; their CCs were removed by repeated pipetting and then washed three times with H‐TALP.…”
Section: Methodsmentioning
confidence: 99%
“…After IVM, about 10 matured COCs per drop were co-incubated with sperm for 5 h at 38.5°C under 5% CO 2 in humidified air. This IVF protocol using a high sperm concentration and a short period of gametes co-incubation was the same used by other authors (Canel et al, 2018;Hiriart et al, 2013;Vichera et al, 2011) and the one we used in previous studies (Barrera et al, 2018;García et al, 2015) | 69 n = 150; IVM-C: n = 150) as previously described (García et al, 2016).…”
Section: In Vitro Fertilization and Embryo Culturementioning
confidence: 99%
“…These results suggest that thermotaxis might have been able to select spermatozoa with the ability to activate the oocyte or decondense the sperm head properly after cytoplasmic injection. We hypothesized that spermatozoa selected by thermotaxis could be properly capacitated and this could be the reason why oocyte activation was not necessary to achieve similar or even higher embryo production rates in comparison to other studies that used ICSI with oocyte activation [50][51][52]. These results are prominent for future studies to optimize the current methodology for bull sperm selection by thermotaxis, which in combination with ICSI and oocyte activation might increase the success of ICSI in this species.…”
Section: Sperm Head Subpopulation Differencesmentioning
confidence: 97%